Seasonal Variability in Regional Ice Flow Due to Meltwater Injection Into the Shear Margins of Jakobshavn Isbræ. Issue 12 (26th December 2017) - Cavanagh, J. P.; Lampkin, D. J.; Moon, T.
Abstract: The impact of meltwater injection into the shear margins of Jakobshavn Isbræ via drainage from water‐filled crevasses on ice flow is examined. We use Landsat‐8 Operational Land Imager panchromatic, high‐resolution imagery to monitor the spatiotemporal variability of seven water‐filled crevasse ponds during the summers of 2013 to 2015. The timing of drainage from water‐filled crevasses coincides with an increase of 2 to 20% in measured ice velocity beyond Jakobshavn Isbræ shear margins, which we define as extramarginal ice velocity. Some water‐filled crevasse groups demonstrate multiple drainage events within a single melt season. Numerical simulations show that hydrologic shear weakening due to water‐filled crevasse drainage can accelerate extramarginal flow by as much as 35% within 10 km of the margins and enhance mass flux through the shear margins by 12%. This work demonstrates a novel mechanism through which surface melt can influence regional ice flow. Key Points: The impacts of hydrologic shear weakening along the margin of Jakobshavn are examined The timing of drainage from water‐filled crevasses coincides with an increase of 2 to 20% in observed extramarginal ice velocity Modeling efforts demonstrate that water‐filled crevasse drainage can accelerate extramarginal ice flow by as much as 35%